Compliance with artesunate and quinine + tetracycline treatment of uncomplicated falciparum malaria in Thailand - W. Fungladda (2018)
A randomized, controlled, malaria-clinic-based field trial was conducted to compare compliance with a 7-day quinine + tetracycline regimen and a 5-day 700-mg artesunate regimen for the treatment of uncomplicated falciparum malaria in a community in Thailand. Of 137 patients, aged 15-60 years attending a malaria clinic, 77 received artesunate and 60 received quinine + tetracycline. Compliance and cure rates were evaluated on days 5 (artesunate) and 7 (quinine + tetracycline) using patient interview/residual pill counts and peripheral blood smear, respectively. Data were analysed using the intention-to-treat approach, and the reasons for compliance and noncompliance were investigated. Compliance was significantly higher (98.4%) with artesunate than with quinine + tetracycline (71.7%) (relative risk adjusted for sex (aRR) = 1.39 (95% C.I. = 1.15-1.68); referent: quinine + tetracycline). Cure rate (100%) was higher in those receiving artesunate than quinine + tetracycline (77.4%) (aRR = 1.32 (95% C.I. = 1.12-1.55)). Reasons for compliance included the desire to be cured and to follow the advice of malaria staff/employer, and the simple dosing regimen. Noncompliance was mostly due to adverse reactions and forgetting to take the drugs. These results can serve as a baseline for designing and evaluating new interventions to improve compliance, as well as for studying cost-effectiveness to help drug policy decision-making. We recommend a strategy which integrates a short-course, once-a-day regimen (with minimal adverse reactions), a better delivery system for antimalarial drugs and health education, and an enhanced advisory role of malaria staff. Considering the higher compliance rate and curative effectiveness of artesunate, we recommend its use instead of quinine + tetracycline for the treatment of uncomplicated malaria in clinics in Thailand. © World Health Organization 1998.